The Value of Sakinah Mawaddah wa Rohmah: Islamic Family Law and Western Perspective on LGBT Narrative - Hassas, Mawloda (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2026)
This study presents a critical and philosophical examination of issues of identity and morality in Islamic law namely sakinah mawaddah wa rohmah value based on classical and contemporary legal books through the lens of LGBTQ stories. It critically approaches the concept of whether the modernist views of sakinah mawaddah wa rohmah, which disenfranchise LGBTQ people, correspond to the moral aims of Shariah, such as justice, dignity, and the avoidance of harm. Based on the foundations of sakinah mawaddah wa rohmah value, care ethics, and queer theory, this research explore on how Islamic law establishes gender identity, its ethical stand on LGBTQ matters, and its relationship with human rights, seeking internal interpretive resources to a more accommodating moral vision. This research method’s strategy is normative. It uses primary legal materials such as Islamic books, Islamic Jurisprudence, and also secondary resources from academic books, Journal articles, UN agencies, and statistical records. The results of this study are first; the foundation of islamic family law ethics and morality; Muslim societies have received guidance from divine revelation and scholarly interpretations of ethical principles which originated from the foundations of Islamic doctrine. Second; Islamic Jurisprudence: Fitrah as Contemporary Interpretation and Identity; Progressive scholars study the Qur’an from a moral accountability perspective alongside the notion of diversity in human sexuality. Third; Western Philosophical Perspectives on LGBTQ Identity and Morality; queer theory aims to do is not to replace Islamic moral reasoning, but to widen its scope. It puts jurists, theologians, and scholars to the test whether the discrimination against LGBTQ individuals lies in the best ethical interest of Islamic law, i.e., justice (Adl), compassion (Raá¸¥ma), and human dignity (KarÄmah).